Kedudukan Filsafat Hukum Dalam Pembentukan Politik Hukum Negara Sebagai Upaya Mewujudkan Keadilan: Kedudukan Filsafat Hukum Dalam Pembentukan Politik Hukum Negara Sebagai Upaya Mewujudkan Keadilan - Farikha Ramadani, Firda; Adiluz Permana, Mario; Kusuma Wardani, Berliana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Legal philosophy plays a strategic role in shaping the direction and orientation of state legal policy, particularly in realizing the ideals of justice. As a branch of philosophy that studies the nature of law, its underlying values, and the purpose of its formation, legal philosophy serves as a normative foundation that guides policymakers so that legal products are not merely legal-formal, but also full of moral and humanitarian values. State legal politics is essentially the state's policy and strategy in forming, implementing, and enforcing laws to achieve certain goals idealized by the constitution. In this context, legal philosophy provides a conceptual framework for determining the principles of justice to be realized, both based on classical theories of justice such as distributive , commutative , and legal justice according to Aristotle, as well as modern theories such as social justice ala John Rawls . The relationship between the two is complementary: legal philosophy provides ethical justification and value direction, while legal politics translates them into applicable positive norms. This research uses a juridical-normative approach with a literature review of legal philosophy theories, legal politics concepts, and the practice of law formation in Indonesia. The study's findings indicate that the absence of a strong philosophical foundation in legal politics has the potential to produce legislation that is unequal, inconsistent, or even contrary to society's sense of justice. Conversely, integrating legal philosophy into the legal policy formulation process can produce a more responsive, humanistic, and just legal system, in accordance with the mandate of the Preamble to the 1945 Constitution and Pancasila as the source of all sources of state law. Thus, legal philosophy is not merely theoretical, but also a crucial instrument in social engineering through law, to ensure the creation of a just, prosperous, and dignified society.